Inquiry-Based Education for Students with Visual Impairment. (4th March 2014) - Rooks-Ellis, Deborah L.
Abstract : The purpose of the study presented here was to identify and synthesize studies of evidence-based practices for working with students with visual impairment in the science classroom. Expanding a comprehensive literature search conducted in 1992, 10 empirical reports were found and reviewed. A synthesis of the results showed strong support for inquiry-oriented approaches to science instruction for children with disabilities. Evidence also was found that knowledge of science pedagogy for children with disabilities is continuing to increase; however, the literature to support evidence-based methodology for students with visual impairment in the science classroom is sparse. This critical review is a call for research that provides support for inquiry approaches in science education for the learner with a visual impairment.